Multifunctional graphene oxide implanted polyurethane ionomer gel electrolyte for quantum dots sensitized solar cell - Kumar S.; Yadav P.K.; Prakash R.; Santra A.; Maiti P. (My University, 2025)
Electrolyte active group (EAG) embedded structured hard segments have been developed via graphene oxide coupled with polyurethane chain. The polysulfide redox couples (S2-/Sn2-) free functionalized polyurethane electrolyte possesses electron donating pendant anions (carboxylate and sulfonate segments) with sufficient oxygenic functional groups on polyurethane backbone. Polyelectrolyte activity is due to elevation of number density of pendant anions (electrolyte active group) into polyurethane chain. Electrochemical impedance spectroscopy (EIS) reveals higher electrical conductivity (4.48 × 10−3 S/cm) for optimized PUI-GO (0.5 wt%) electrolyte. The electrolyte active groups are prone to facilitate photovoltaic reaction due to synergistic interaction and function with MPA capped CdS. The QDSSC (FTO-RGO/TiO2/MPA-CdS/PUI-GO/FTO-Pt) exhibits maximum power conversion efficiency (1.63 %) and open circuit potential (VOC = 0.594 V) under 1 sun (100 mW/cm2) photo illumination. VOC is found to be improved with PUI-GO electrolyte due to its multi-functional activities such as expanded electrocatalytic area, conducting nanochannel and interfacial passivation effect of carboxylate ion on photoanode. © 2022 Elsevier B.V.